Pengaruh Leverage, Profitabilitas, Ukuran Perusahaan, dan Growth Terhadap Nilai Perusahaan - Elinda Kurnia Agilita; Lintang Kurniawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of leverage, profitability, firm size, and growth on firm value in the consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. The research adopts a quantitative approach with a causal associative strategy. The research sample was obtained using purposive sampling with specific criteria, while secondary data were collected from financial reports and official IDX sources. Data analysis was conducted using multiple regression, preceded by descriptive statistical analysis and classical assumption tests. The results indicate that leverage and profitability significantly influence firm value, where high leverage attracts investors and increases stock demand, while high profitability reflects asset management efficiency in creating firm value. However, firm size does not have a significant impact on firm value, as a larger scale does not necessarily guarantee better access to capital. Additionally, firm growth does not significantly influence firm value since rapid expansion may increase investment needs, which can suppress firm value. This study has limitations in terms of sector scope, research period, and the variables used. Therefore, future research is recommended to expand the industrial sector coverage, extend the research period, and incorporate additional variables such as market risk, corporate governance, and macroeconomic factors to gain a more comprehensive understanding of the factors affecting firm value.